THEORETICAL ANALYSIS OF THE EFFECTS OF COUNTERIONS ON THE SUPRAMOLECULAR ARRANGEMENT OF SULFAMETHOXAZOLE (CIPEEX, 2022)
SULFAMETHOXAZOLE (SMZ) IS A SULFONAMIDE THAT ACTS BY COMPETITIVELY INHIBITING THE FORMATION OF FOLATE FROM P-AMINOBENZOIC ACID (PABA). IN A DRUG DEVELOPMENT PROCESS, SALT FORMATION IS A STRATEGY TO MODULATE ITS PHARMACOKINETIC AND PHYSICOCHEMICAL PROPERTIES, SUCH AS: AQUEOUS SOLUBILITY, DISSOLUTION, PURITY, STABILITY AND TOXICITY. AMONG THE ACTIVE PHARMACEUTICAL INGREDIENTS MARKETED IN SALT FORM, SULFAMETHOXAZOLE BELONGS TO THE CLASS OF SULFONAMIDES WIDELY USED IN THE TREATMENT OF URINARY TRACT INFECTIONS (PROHOTSKY; ZHAO, 2012). SULFAMETHOXAZOLE HAS LOW BIOAVAILABILITY, LOW PERMEABILITY AND LOW SOLUBILITY, IN ADDITION TO PRESENTING LOW ABSORPTION BY THE INTESTINAL MUCOSA AND GREAT VARIABILITY IS EXPECTED (ALSUBAIE ET AL., 2018). IN THIS SENSE, A PHARMACEUTICAL STRATEGY TO OVERCOME THESE CHALLENGES IS TO PROMOTE ITS FORMULATION IN THE FORM OF SALT.
Keywords: supramolecular; theoretical analysis; sulfamethoxazole